Cover Feature: Preparation, Properties, and Application of Lignocellulosic‐Based Fluorescent Carbon Dots (ChemSusChem 8/2022). Issue 8 (1st April 2022) - Song, Xueping; Zhao, Siyu; Xu, Ying; Chen, Xinrui; Wang, Shuangfei; Zhao, Peitao; Pu, Yunqiao; Ragauskas, Arthur J.
Abstract : The Cover Feature shows a kind of fluorescent carbon dots (LC‐CDs) prepared from natural lignocellulose materials. LC‐CDs present spherical nanoparticles of graphite oxide‐like structure with good physicochemical stability. They also display excellent optical properties such as photoluminescence, fluorescence quenching, and multicolor fluorescence, which could be widely applied in the field of bioimaging, sensors, and catalysis. More information can be found in the Review by X. Song et al .